Determination of suitable osmotic solution concentration and time for osmotic dehydration of papaya slices - Mahendranathan, M.; Prasantha, B.D.R.; Hettiarachchi, D.N. (University of Jaffna, 2019)
Osmotic dehydration has been used as a long term preservation method for papaya slices. This study was done to determine suitable sugar concentration and time for osmotic dehydration of papaya. In this study papaya slices (50×50×5 mm) were blanched for three minutes, then pre weighed pieces were dipped into 40o Brix, 50o Brix, and 60o Brix sugar solutions for four hours and weighed every 30 minutes with 15 minutes interval manual agitation. Based on the rate of weight changes, suitable concentration of sugar solution was selected. During the process mean percentage weight loss of papaya were increased with time. Significant differences of mean weight loss of papaya were not observed in sugar concentrations 50o and 60o Brix. Whereas it showed significant difference with 40o Brix, while all other conditions were maintained constant. Due to case hardening effect and high cost of production 60o Brix was rejected. Result of this study proved that 50o Brix for four hours period is the suitable condition for the effective osmotic dehydration of papaya slices.
Keywords: Osmotic dehydration; Papaya; sugar concentration